IMPLEMENTATION OF TAHFIDZ AL-QUR'AN PROGRAM AT BOARDING SCHOOL SMPTQ ABI UMMI BOYOLALI - Abid Nurhuda; Abdullah Hadziq (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
The Tahfidz Al-Qur'an program has many functions, one of which is to strengthen the character and religious values of students, especially in the era of globalization which is very vulnerable to cultural shifts and moral degradation. so that many public and private educational institutions hold tahfidz programs in the hope that if students are close to the Qur'an they will have good morals and personality. One of them is SMPTQ Abi Ummi Boyolali based on the Boarding School and its flagship program is Tahfidz Al-Qur'an which targets to memorize 5 Juz within 1 year. The purpose of this study was to describe how the implementation of the tahfidz Al-Qur'an program at the Boarding School of SMPTQ Abi Ummi Boyolali. The method used is descriptive qualitative with data collection using observation, Interviews and documentation from September 2021-December 2021 were analyzed, presented and finally concluded. The result is that the implementation of the Tahfidz Al-Qur'an Program at the Boarding School of SMPTQ Abi Ummi Boyolali is quite ideal because it includes determining the time, environment, place, material and various methods. Then there is the direct involvement of musyrif tahfidz, upgrading abilities and recruiting to a standard. As well as the support of parents through the role of the school. And finally the control from superiors.